THE STUDY OF FREE RADICAL PROCESSES AND THE CONTENT OF CYTOKINES IN LIVER ECHINOCOCCOSIS - H. V. Zanginyan (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The purpose of this study is to investigate the activity of lipid peroxidation and oxidative modification of proteins, determination of nitric oxide in relation to the content of cytokines in hepatic echinococcosis in humans before and after surgical intervention. Our data suggest that in the development of the pathogenesis of echinococcosis the activation of free radical reactions as well as increase in nitric oxide and cytokines play certain role.